Long-COVID-19 syndrome: an overview - Potpara, Tatjana (Medicinski podmladak, 2023)
The Long-COVID-19 syndrome has emerged as global epidemic, affecting individuals after an acute infection caused by the Severe acute respiratory syndrome coronavirus 2, impacting multiple organs, including the heart. The most common symptoms encompass fatigue and shortness of breath, which could persist for months after an acute COVID-19 infection. Numerous studies have researched the pathophysiology of Long-COVID-19 syndrome, suggesting that local tissue damage and hyperinflation could be employed as possible mechanisms of Long-COVID-19 syndrome. Many blood biomarkers (blood urea nitrogen, D-dimer, lymphopenia, troponin-1, interleukin-6, and CRP) and clinical risk factors (CRP female sex, a history of psychiatric disorders, and the presence of more than five symptoms during the first week of an acute illness) are shown to be associated with the development of Long-COVID-19 syndrome. Currently, the evidence-based specific pharmacological treatments for the Long-COVID-19 syndrome are lacking. Several studies have shown an association between antiviral drugs (such as nirmatrelvir, ensitrelvir, and molnupiravir) and vaccination against COVID-19 with a reduced risk of developing Long-COVID-19 syndrome. This narrative review discusses the possible pathophysiology, risk factors, and treatments for Long-COVID-19 syndrome with particular reference to the cardiovascular system.